A Novel Role for DNA Hydroxymethylation in Sexual Differentiation of the Mouse Brain - Cisternas, Carla Daniela (2019)
Fil: Cisternas, Carla Daniela. Universidad Nacional de Córdoba. Facultad de Odontología. Cátedra de Biología Celular; Argentina.